Development and validation of the athletes` rights survey - Tuakli-Wosornu, Y. A.; Goutos, D.; Ramia, I.; Galea, N. M.; Mountjoy, M.; Grimm, K.; Bekker, S. (BMJ Open Sport & Exercise Medicine, 2021)
A recognised imbalance of power exists between athletes and sporting institutions. Recent cases of systemic athlete abuse demonstrate the relationship between power disparities and harassment and abuse in sport. Embedding human rights principles into sporting institutions is a critical step towards preventing harassment and abuse in sport. In 2017, the World Players Association (WPA) launched the Universal Declaration of Player Rights. A year later, the International Olympic Committee (IOC) developed their Athletes` Rights and Responsibilities Declaration. These two documents codify benchmarks `for international sporting organisations to meet their obligations to protect, respect and guarantee the fundamental rights of players`. This paper is the first project exploring athletes` knowledge, understanding and awareness of rights in the sports context. This study presents the development and validation of a survey investigating athletes` knowledge of these declarations, associated attitudes/beliefs and understanding of how these rights can be enacted in practice. The survey includes 10 statements of athlete rights based on the WPA and IOC declarations. Face validation was assessed by distributing the survey to 10 athletes and conducting qualitative interviews with a subgroup of four athletes. The survey was reworked into 13 statements, and the tool was validated with 611 responses through confirmatory factor analysis. Key findings include a weak correlation between athletes` knowledge and their attitudes/beliefs, and challenges with the interpretation of words such as `pressure,` `violence,` `harassment` and `intimidation.` This validation puts forward the first survey instrument to directly test athletes` knowledge, attitudes and beliefs about rights in sport.